2022
DOI: 10.4103/idoj.idoj_58_22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Latex Glove Allergy among Healthcare Workers in a Tertiary Care Center In South India - A Cross-Sectional Study

Abstract: Background: Latex glove allergy and its impact on healthcare workers (HCWs) have been studied in many countries, but the data is scarce from developing countries. Objectives: We wanted to estimate the prevalence and patterns of latex glove allergy among HCWs and to study the factors associated with it. Materials and Methods: We conducted a cross-sectional study among 1088 HCWs of a tertiary care center in South India with the screening questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…While many allergies initially present in childhood, chronic workplace allergen exposure can result in adult sensitization, for example, as occurs in woodmill workers, fish packers, and bakers, the latter continually exposed to wheat flour, 78 , 79 , 80 presumably via inhalational exposure. Healthcare workers that use latex gloves over long time periods are also at increased risk of developing latex allergies, 81 presumably from exposure through the skin. We suggest that what we most closely approximate in mouse allergy models relying on long‐term repeated unadjuvanted allergen exposures, such as aerosolization of ovalbumin, are these chronic workplace exposures, where repeat challenge maintains a low‐level IgE response for long periods.…”
Section: How Does Sensitization Happen?mentioning
confidence: 99%
See 1 more Smart Citation
“…While many allergies initially present in childhood, chronic workplace allergen exposure can result in adult sensitization, for example, as occurs in woodmill workers, fish packers, and bakers, the latter continually exposed to wheat flour, 78 , 79 , 80 presumably via inhalational exposure. Healthcare workers that use latex gloves over long time periods are also at increased risk of developing latex allergies, 81 presumably from exposure through the skin. We suggest that what we most closely approximate in mouse allergy models relying on long‐term repeated unadjuvanted allergen exposures, such as aerosolization of ovalbumin, are these chronic workplace exposures, where repeat challenge maintains a low‐level IgE response for long periods.…”
Section: How Does Sensitization Happen?mentioning
confidence: 99%
“… 137 , 138 , 139 , 143 , 148 As discussed earlier, false positives in IgE + cell fractions requires careful subsetting to avoid. 148 If “IgE + ” cells are not significantly less abundant than IgG + cells, loosely reflecting the serum antibody differential (100‐2000‐fold lower for IgE than IgG 81 ), probably there is contamination in the gate. Further, IgE + ASC show a CXCL12 homing defect, placing them at a disadvantage at seeding in bone marrow, which may suggest ASC in other tissues could equally contribute to ongoing IgE production.…”
Section: The Life Spans Of Ige + Ascmentioning
confidence: 99%
“…A recent Argentine study showed a latex sensitization prevalence of 7.96% (95% confidence interval: 3.70–14.58) among physicians in a children’s hospital [ 21 ]. Latex allergy is an emerging problem in developing countries as well: recent studies reported latex hypersensitivity in 9.1% of healthcare workers in South India [ 22 ] and in 9.2% of Turkish healthcare workers [ 23 ].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…For Type IV immunologic reactions, rubber chemicals added to the rubber gloves during processing, that is, vulcanizing agents, accelerators, antioxidants, organic pigments, and glove powders, are known to be the responsible allergens. This is a delayed‐type allergy which accounts for most reactions to gloves 3–5 . Among the compounding ingredients, accelerators are considered the most important contact allergens in gloves.…”
Section: Introductionmentioning
confidence: 99%